2019
DOI: 10.1272/jnms.jnms.2018_86-402
|View full text |Cite
|
Sign up to set email alerts
|

Increased H19 Long Non-coding RNA Expression in Schwann Cells in Peripheral Neuropathic Pain

Abstract: Background: Neuropathic pain is an intractable chronic pain condition caused by damage to the somatosensory system. Although non-coding RNAs such as microRNAs are important regulators of neuropathic pain, the role of long non-coding RNAs (lncRNAs) is poorly understood. Methods: This study used a rat model of neuropathic pain induced by lumbar fifth spinal nerve ligation (SNL). Microarray analysis of lncRNAs in the lumbar fifth dorsal root ganglion was performed at day 14 after SNL. Expression levels of H19 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…27 In a previous study, it was discovered that in NP patients, H19 was consistently increased in Schwann cells from the peripheral axon in the primary sensory neurons, suggesting that H19 played a pivotal role in NP pathogenesis. 10 In this study, we hypothesized that there is a mechanism of H19 in NP regulating CDK5 and CREB phosphorylation. Consequently, our data showed that silencing H19 mitigated NP by downregulating CDK5-mediated CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…27 In a previous study, it was discovered that in NP patients, H19 was consistently increased in Schwann cells from the peripheral axon in the primary sensory neurons, suggesting that H19 played a pivotal role in NP pathogenesis. 10 In this study, we hypothesized that there is a mechanism of H19 in NP regulating CDK5 and CREB phosphorylation. Consequently, our data showed that silencing H19 mitigated NP by downregulating CDK5-mediated CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 97%
“…9 H19 expression is increased in Schwann cells of the NP model after spinal nerve ligation. 10 Typically, CDKs that are activated together with a regulatory subunit tend to be proline-guided serine protein kinases. 11 However, CDK5 mainly functions in the central nervous system instead of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…is time-dependent and varies between strains and species [182,183,185]. LncRNAs play important roles in neuropathic pain processes not only in neurons, but also in non-neuronal cells, such as Schwann cells, satellite glial cells, macrophages and microglia [74,83,185,[188][189][190][191].…”
Section: Lncrnas As Possible Signatures For Pain Disordersmentioning
confidence: 99%
“…They relieved hyperalgesia and decreased neuroinflammation by modulating the P2X 3 receptor or P2X 7 receptor. In addition to the lncRNAs reported above, some lncRNAs have also been reported to be associated with NP [19,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138].…”
Section: Lncrnas and Npmentioning
confidence: 99%